2012
DOI: 10.4028/www.scientific.net/ssp.190.361
|View full text |Cite
|
Sign up to set email alerts
|

Features of Magneto-Optical Response on Multilayer Nanostructures {(Co<sub>45</sub>Fe<sub>45</sub>Zr<sub>10</sub>)<sub>Z</sub>(Al<sub>2</sub>O<sub>3</sub>)<sub>100-Z</sub>/α-Si:H}<sub>n</sub>

Abstract: Spectral and field dependencies of Transversal Kerr Effect (TKE) for [(Co45Fe45Zr10)Z(Al2O3)100-Z(X)/α-Si:H(Y)] n multilayers have been studied in the energy range 0.5 - 4.0 eV. It was found that TKE field dependencies in the nearest IR energy range exhibit anomalous behavior for structures only with thin Si layers and this behavior vanishes with increasing of the Si layer thickness. TKE spectra measured in small and large magnetic fields were essentially different. It was shown that magneto-optical response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…1) that was considerably different from δ(Н) curves found for bulk metal-insulator nanocomposite [6]. The similar pattern was observed for the same chemical composition films, where nanocomposite had been before percolation threshold [1][2][3]. In some cases δ(Н) curves reveal anomalies, such as the TKE sign reversal and the presence of local minimum of the effect in the small fields (Н < 100 Oe).…”
Section: Experimental Details and Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…1) that was considerably different from δ(Н) curves found for bulk metal-insulator nanocomposite [6]. The similar pattern was observed for the same chemical composition films, where nanocomposite had been before percolation threshold [1][2][3]. In some cases δ(Н) curves reveal anomalies, such as the TKE sign reversal and the presence of local minimum of the effect in the small fields (Н < 100 Oe).…”
Section: Experimental Details and Resultssupporting
confidence: 50%
“…Active phase interaction makes difficulties in obtained results interpretation and limits the possibilities of application of the materals mentioned above. Previous studies of multilayer structures (ML) nanocomposites-silicon [(Co 45 Fe 45 Zr 10 ) Z (Al 2 O 3 ) 100-Z (X)/Si(Y)] n [1][2][3], where composite had been before percolation threshold, shown that silicon introduction led to anomalous behavior of electrical, magnetic and magneto-optical properties of ML with small thickness of Si (<2nm). In [3] supposed that TKE spectra and field dependences anomalies related with contributions competition between two composites: (Co 45 Fe 45 Zr 10 )+Al 2 O 3 +Si+Silicides and (Co 45 Fe 45 Zr 10 )+Si+Silicides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magneto-optical methods have several advantages, unlike optical ones, such as sensitivity to the presence of magnetic inhomogeneities, a particle shape and size changes, their volume distribution, and appearance of new magnetic phases in a nanostructure. Previous studies of nanocomposite-silicon multilayers [(Co 45 Fe 45 Zr 10 ) Z (Al 2 O 3 ) 100-Z (X)/Si(Y)] n [7][8][9] with composite concentrations near and under the percolation threshold have shown that the addition of silicon layers leads to anomalous behaviour of electrical, magnetic and magneto-optical properties of ML with small thickness of Si (< 2nm). In [9] it was assumed that TKE spectra and anomalies in field dependences were related to competition of contributions from several magnetic phases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of nanocomposite-silicon multilayers [(Co 45 Fe 45 Zr 10 ) Z (Al 2 O 3 ) 100-Z (X)/Si(Y)] n [7][8][9] with composite concentrations near and under the percolation threshold have shown that the addition of silicon layers leads to anomalous behaviour of electrical, magnetic and magneto-optical properties of ML with small thickness of Si (< 2nm). In [9] it was assumed that TKE spectra and anomalies in field dependences were related to competition of contributions from several magnetic phases. In the present work we focus on MO properties of nanocomposite-semiconductor multilayers (CoFeB) z (SiO 2 ) 100-z /Si and (CoFeB) z (SiO 2 ) 100-z /C with Z = 33.9 and 40 at.% a in order to trace the influence of the chemical composition and the thickness of ML layers on their MO behavior.…”
Section: Introductionmentioning
confidence: 99%